PERFORMANCE ANALYSIS AND SAFETY SYSTEM OF BATTERY PACK NMCAND 2W - ELECTRIC MOTORCYCLES BASED ON SAE J2982_2022 STANDARD - Waraqa Santoso, Yusuf
Abstract - In 2025, President Joko Widodo of the Republic of Indonesia aims for the production of 2 million electric motorcycles in Indonesia. This aligns with the Indonesian government's commitment to reduce CO2 emissions by 29% independently and by 41% with international support by 2030. The decarbonization program is being pursued because Indonesia has agreed to adhere to the 2015 Paris Agreement, which sets a goal to limit global warming to a maximum of 1,5°C - 2°C. The acceleration of electric vehicle adoption must prioritize safety standards for these vehicles. This research uses an NMC Battery Pack with a capacity of 1800 Wh and an electric motorcycle with specifications of 2 kW rated / 3 kW peak power and a load weight of 75 kg. The testing standard used is SAE J2982_2022, selected because it is based on urban driving cycles characterized by stop -and-go conditions. The SAE J2982_2022 test was conducted on a dynamometer. The outputs of this test include energy consumption characteristics, operating temperature, current consumption, power output of the battery pack, and the power at the rear wheel of the electric motorcycle during constant speed use, as well as whether any system failure warnings were detected. The test results showed an average energy consumption of (25,02 ± 0,92) Wh/km, an operating temperature range of 30,2°C – 45,3°C, a constant speed of (57,88 ± 0,63) km/h, a current consumption of (19,3 ± 0,87) A, battery power of (1,51 ± 0,09) kW, and rear wheel power of (1,28 ± 0,23) kW, resulting in a battery-to-wheel efficiency of 84,77%. During the testing, the battery pack operated safely without any active system failure warning indicators.